2016
DOI: 10.1097/iae.0000000000001050
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Choroidal and Retinal Lesions in Posterior Uveitis by Multispectral Wide-Field Scanning Laser Ophthalmoscopy

Abstract: Retinal and choroidal lesions in patients with posterior uveitis can be differentially visualized with Optos 532 nm and 635 nm lasers, respectively, allowing determination of depth of pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…lwBAF (488 nm excitation wavelength) can be used as an imaging tool to monitor patients in terms of disease progression during treatment [41]. Some data suggest that a larger number of choroidal lesions can be identified using a laser with 635 nm excitation wavelength compared to 532 nm [42]. Interestingly, macular hyperfluorescent lesions are not associated with worse LogMAR visual acuity [43].…”
Section: Serpiginous Choroiditis (Sc)mentioning
confidence: 99%
“…lwBAF (488 nm excitation wavelength) can be used as an imaging tool to monitor patients in terms of disease progression during treatment [41]. Some data suggest that a larger number of choroidal lesions can be identified using a laser with 635 nm excitation wavelength compared to 532 nm [42]. Interestingly, macular hyperfluorescent lesions are not associated with worse LogMAR visual acuity [43].…”
Section: Serpiginous Choroiditis (Sc)mentioning
confidence: 99%
“…Similarly, Knickelbein et al . [ 68 ] demonstrated that a higher percentage of patients with birdshot choroidopathy had lesions seen on 635 nm imaging than 532 nm as this is primarily a choroidal inflammatory disorder.…”
Section: Ultra-wide Field Imagingmentioning
confidence: 99%
“…Birdshot chorioretinopathy (BCR), which has also been referred to as vitiliginous chorioretinitis, is an inflammatory posterior uveitic syndrome characterized by deep small-to-medium-sized round or oval hypopigmented choroidal lesions radiating from the optic nerve in a pattern similar to birdshot from a shotgun ( Figure 1 ) [ 3 , 4 ]. Birdshot lesions are easily detected by the 635 nm laser on Optos ® imaging as perivascular choroidal lesions ( Figure 1 ) [ 5 ]. ICGA shows characteristic hypofluorescent choroidal spots that correspond to and are typically greater in number than the clinically apparent lesions during active disease ( Figure 2 ) [ 6 ].…”
Section: Birdshot Chorioretinopathymentioning
confidence: 99%